Serum fatty acid profiles in systemic lupus erythematosus and patient reported outcomes: The Michigan Lupus Epidemiology & Surveillance (MILES) Program - Gilley, Kristen N.; Fenton, Jenifer I.; Zick, Suzanna M.; Li, Kexin; Wang, Lu; Marder, Wendy; McCune, W. Joseph; Jain, Raghav; Herndon-Fenton, Sidney; Hassett, Afton L.; Barbour, Kamil E.; Pestka, James J.; et al. (Frontiers in Immunology, 2024)
IntroductionDespite progress in systemic lupus erythematosus (SLE) treatment, challenges persist in medication adherence due to side effects and costs. Precision nutrition, particularly adjusting fatty acid intake, offers a cost-effective strategy for enhancing SLE management. Prior research, including our own, indicates that increased consumption of omega-3 polyunsaturated fatty acids (PUFAs) correlates with improved outcomes in SLE patients. Here we build upon these findings by investigating associations between serum fatty acids—grouped as PUFAs, monounsaturated fatty acids (MUFAs), and saturated fatty acids (SFAs)—and lupus activity, pain, and sleep disturbance.MethodsUsing data from 418 participants with SLE in the Michigan Lupus Epidemiology and Surveillance (MILES) Cohort, we examined associations between serum levels of 25 fatty acids determined by GC-MS and patient-reported outcomes. Disease activity, pain, and sleep quality were assessed using standardized questionnaires. Generalized additive models and partial residual plots were utilized to examine the linearity of fatty acid effects. Variable selection was performed using Least Absolute Shrinkage and Selection Operator (LASSO), followed by multiple linear regression adjusting for sociodemographic factors.ResultsFindings indicated favorable associations between ω-3 PUFAs—and, to a lesser extent, ω-6 PUFAs—and patient-reported outcomes, while MUFAs and SFAs showed unfavorable associations. Docosahexaenoic acid (DHA), an omega-3 PUFA, exhibited the most robust favorable associations across all outcomes. Additionally, the omega-3 α-linolenic acid (ALA) was linked to reduced pain, whereas eicosapentaenoic acid (EPA), another omega-3, was associated with worsened disease activity and pain. Among omega-6 PUFAs, dihomo-γ-linolenic acid (DGLA) was favorably associated with disease activity, while the omega-9 PUFA Mead acid was linked to increased pain.DiscussionThese findings underscore the prospect that increased tissue levels of long-chain omega-3 PUFAs, particularly DHA, are favorably associated with SLE outcomes. Although further research is needed to establish causal relationships, existing evidence supports the role of omega-3 PUFAs in managing cardiovascular and chronic kidney disease, common SLE comorbidities. Most study participants exhibited low omega-3 PUFA status, suggesting substantial potential for improvement through targeted dietary interventions and supplementation. This study supports a potential role for precision nutrition in comprehensive SLE management, considering the impact of PUFAs, SFAs and MUFAs.